The Phenotypic and Genetic Underpinnings of Flower Size in Polemoniaceae - Landis, Jacob B.; O'Toole, Rebecca D.; Ventura, Kayla L.; Gitzendanner, Matthew A.; Oppenheimer, David G.; Soltis, Douglas E.; Soltis, Pamela S. (Frontiers in Plant Science, 2016)
Corolla length is a labile flower feature and has strong implications for pollinator success. However, the phenotypic and genetic bases of corolla elongation are not well known, largely due to a lack of good candidate genes for potential genetic exploration and functional work. We investigate both the cellular phenotypic differences in corolla length, as well as the genetic control of this trait, in Saltugilia (Polemoniaceae). Taxa in this clade exhibit a large range of flower sizes and differ dramatically in pollinator guilds. Flowers of each species were collected from multiple individuals during four stages of flower development to ascertain if cell number or cell size is more important in determining flower size. In Saltugilia, flower size appears to be driven more by cell size than cell number. Fully mature flowers of all taxa contain jigsaw cells similar to cells seen in sepals and leaves; however, these cells are not typically found in most developing flowers. The proportion of this cell type in mature flowers appears to have substantial implications, comprising 17% to 68% of the overall flower size. To identify candidate genes responsible for differences in cell area and cell type, transcriptomes were generated for two individuals of the species with the smallest (S. australis) and largest (S. splendens subsp. grantii) flowers across the same four developmental stages visualized with confocal microscopy. Analyses identified genes associated with cell wall formation that are up-regulated in the mature flower stage compared to mid-stage flowers (75% of mature size). This developmental change is associated with the origin of jigsaw cells in the corolla tube of mature flowers. Further comparisons between mature flowers in the two species revealed 354 transcripts that are up-regulated in the large-flowered S. splendens subsp. grantii compared to the small-flowered S. australis. These results are likely broadly applicable to Polemoniaceae, a clade of nearly 400 species, with extensive variation in floral form and shape.